2021
DOI: 10.3390/jcm10173962
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Neural Interface When Using Modiolar Electrode Stimulation. Radiological Evaluation, Trans-Impedance Matrix Analysis and Effect on Listening Effort in Cochlear Implantation

Abstract: Background: The proximity of the electrode to the modiolar wall may be of interest to investigate the effect of pitch discrimination. This research establishes the relation between these factors and whether perimodiolar positions may provide benefits regarding improved electrode discrimination. Methods: A prospective randomized study including 24 post-lingual deaf adults was performed. A psychoacoustic study was done by using a psychoacoustic research platform. Radiological study, and a cone-beam computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 33 publications
1
19
0
2
Order By: Relevance
“…The clinical study is consistent with the result of the simulation. The modiolar electrode had better hearing preservation than midscala or lateral electrode (100). However, some results have shown that the electrode-modiolus distance does not affect the stimulation threshold (101).…”
Section: Models For the CImentioning
confidence: 91%
“…The clinical study is consistent with the result of the simulation. The modiolar electrode had better hearing preservation than midscala or lateral electrode (100). However, some results have shown that the electrode-modiolus distance does not affect the stimulation threshold (101).…”
Section: Models For the CImentioning
confidence: 91%
“…Increased channel independence, decreased power consumption, and improved pitch placement has also been reported in SME arrays compared to lateral wall arrays 18 . A closer neural‐electrode interface may result in better electrode discrimination and lower listening effort 19 . The literature is mixed on the best outcomes by the electrode, with some favoring 1 array 11,17,20 versus others that show no significant difference in performance 7,21 …”
Section: Discussionmentioning
confidence: 99%
“…18 A closer neural-electrode interface may result in better electrode discrimination and lower listening effort. 19 The literature is mixed on the best outcomes by the electrode, with some favoring 1 array 11,17,20 versus others that show no significant difference in performance. 7,21 HP Rates and Threshold Shift Comparisons to the Literature Published HP success rates can be somewhat challenging to interpret, as HP studies often differ on a myriad of parameters: HP definition, electrode length and array designs used, degree of partial versus full insertion, variable inclusion criteria, variable surgical technique, and reported time intervals.…”
Section: Sme Versus Slwe Design and Implicationsmentioning
confidence: 99%
“…Bei Somit ergeben sich unterschiedliche Feldausbreitungen, welche zu verschiedenen "spread of excitations" (SOE) führen können. Hierdurch entsteht eine unterschiedliche Selektivität der Stimulation für verschiedene Frequenzen, was zu psychoakustisch wirksamer, verschlechterter Frequenzwahrnehmung des Patienten führen kann und somit letztendlich eine Auswirkung auf das Sprachverstehen hat [1,11,12]. Durch neuere Techniken wie der intraoperativen Durchleuchtung während der Implantation könnte in Zukunft eine visuelle Kontrolle der Lage der Elektrode in der Cochlea erfolgen, und der Chirurg wäre in der Lage, besonders große Unterschiede durch feinste Bewegungen zu korrigieren [13].…”
Section: Materials Und Methodenunclassified
“…In dung und geringere kognitive Höranstrengung haben, und postulierten einen Vorteil einer perimodiolären Lage [11,14]. Hierbei zeigt sich als Unterschied zu unserer Studie, dass es sich nicht um ein gematchtes Patientenkollektiv sowie um eine kleinere Patientenzahl handelt.…”
Section: Materials Und Methodenunclassified